IMPLEMENTATION OF ACCOUNTING IN FINANCIAL CONTROL IN ELVALA BAWANG DISTRIBUTOR MSME’S IN KRIAN DISTRICT - Ayu Kurniawati Aplan; Nihlatul Qudus Sukma Nirwana (International Journal of Economic Integration and Regional Competitiveness, 2026)
Abstract. MSME’s have an import role in the Indonesian economy admist increasingly Competition in the global economy but still face obstacles such as limited capital san low understanding of accounting so that financial recording is not yet optimal. Therefore, the implementation of good accounting and financial control is very necessary so that businesses are more efficient, transparent, reduce financial risk and support business decision-making for MSME’s owner. This study aims to identify and analyze the extent to which accounting implementation support financial control in MSME’s. That research reveals that accounting practices remain rudimentary and do not yet comply with established accounting standarts where accounting is still done simply. Thus Financial  control is not yet running optimal due to the absence of a structured recording system. Monitoring of cash flow and inventory remain weak, leading to a potential for error and fund leages. Improvements in the recording system and an increase in accounting understanding are required to make financial control effective.